DIVERGENT WOMEN interdisciplinary perspectives on female deviance and dissent. (Emerald interdisciplinary connexions, 2022)
A 'good woman' is hard to find. To be 'good', after all, women face expectations that are shifting, internally contradictory, emotionally extreme, and prospectively even deadly. To be divergent, on the other hand, is an expansive position, encompassing cackling witches, childfree women, struggling mothers, insecure teenagers, and persecuted innocents. Exploring divergent women from a variety of critical and creative perspectives, this edited collection puts forth a dialogic discussion of how non-conforming women are coded as 'evil', and asks, what happens when women choose to be divergent? Delving into reflective and auto-ethnographic perspectives which explore subjective responses to the influence of the representation and treatment of evil women, Divergent Women is ultimately a celebratory reclamation of the concept of feminine transgression. Featuring perspectives from North Korea to Victorian England, from Biblical to digital narratives, this boundary breaking text demonstrates that divergent women have complex inner lives, agencies, and a unique ability to inspire other women to resist social sanctions. Encompassing global perspectives and bringing together artistic and academic work, the authors invite readers to explore the possibilities for divergence that exist under the label of womanhood.